2021
DOI: 10.1039/d0bm01247e
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental determinants of organized iPSC-cardiomyocyte tissues on synthetic fibrous matrices

Abstract: This work provides microenvironmental design parameters to optimize iPSC-cardiomyocyte tissues formed on tunable synthetic matrices that mimic myocardial ECM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 68 publications
(136 reference statements)
0
47
0
Order By: Relevance
“…Thus, cells could interact with both structural components without altering expression of integrin subtypes. DexVS fibers can be readily functionalized with other thiolated peptides via Michael-type addition, including GxOGER to model stromal type I collagen and other full-length proteins 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, cells could interact with both structural components without altering expression of integrin subtypes. DexVS fibers can be readily functionalized with other thiolated peptides via Michael-type addition, including GxOGER to model stromal type I collagen and other full-length proteins 38 .…”
Section: Discussionmentioning
confidence: 99%
“…These properties are very attractive for tissue engineering. Indeed, in [ 128 ], iPSC-CMs were seeded on electrospun dextran vinyl sulfone (DVS) fibers with varying biochemical, architectural, and mechanical properties, and it was shown that the optimal configuration was fibronectin-functionalized DVS matrices with highly aligned fibers and low stiffness. The tissues generated on these scaffolds even demonstrated better maturation than micropatterned fibronectin lines.…”
Section: Cardiac Organoids To Reproduce the Features Of Human Cardiac Tissuementioning
confidence: 99%
“…While RGD was used to enable cell adhesion to fiber segments here, other ECM peptides can be used to model full length proteins such as the GXOGER sequence of type I collagen ( DePalma et al, 2021 ). As DVS fiber segments are not hydrolytically or proteolytically degradable, cell force-mediated reorganization of fibrous architecture could also be investigated.…”
Section: Discussionmentioning
confidence: 99%